Nivel de inclusión financiera y su relación con el crecimiento de la economía del hogar en padres de familia de la Facultad de Ciencias Económicas y de Negocios Iquitos año 2024 - Ramírez Calderón, Juan Alejandro (2025)
Financial inclusion has garnered significant attention from academia and governments in recent decades due to its facilitating role in sustainable development by enabling individuals to integrate into the financial system. An extensive body of literature underscores the necessity of examining financial inclusion in various contexts. In this regard, the present study aimed to identify the relationship between financial inclusion and household economic growth (measured in two versions) among parents of the Faculty of Economic and Business Sciences in Iquitos in 2024. A Likert-scale questionnaire (1–5) was administered to a sample of 210 responses drawn from a population of 2,313 individuals. In RStudio, the correlation was analyzed using Spearman’s coefficient ( = 0.6164 and = 0.6099, with a p-value = 0) and Kendall’s coefficient ( = 0.4642 and 0.4554, with a p-value = 0), supported by a Bootstrap analysis (B = 20,000) that did not reveal any confidence interval containing zero. The study concludes that there is a moderate-to-high, positive, and statistically significant correlation between household economic growth and financial inclusion. Although all dimensions of financial inclusion exhibited a moderate association, the use of bank accounts slightly outperformed the use of formal credit and mobile applications.